Possible origin of RHIC Rout/Rsid HBT results - Padula, Sandra S. [UNESP] (Elsevier, 2003)
The effects of opacity of the nuclei together with a blackbody type of emission along the system history are considered as a means to explain the ratio Rout/Rsid observed by STAR and PHENIX collaborations at RHIC. Within our model, no flow is required to explain the data trend of this ratio for large surface emissivities. © 2003 Elsevier Science B.V. All rights reserved.